A Case Report of an Adolescent with Anomalous Origin of the Left Coronary Artery from the Pulmonary Trunk (ALCAPA) - Momenuzzaman, NA; Rima, Rezoana (Cardiovascular Journal, 2012)
Anomalous origin of the left coronary artery from the pulmonary artery is a serious congenital cardiac defect associated with high mortality rates in infancy. It is undoubtedly a rare defect but its diagnosis during life is possible in most cases, and successful surgery appears within reach. The object of this paper is to report our experience with a fourteen years old girl with this rare anomaly. The presenting symptoms of our patient during infancy were not that are considered classic for this anomaly. Though the child had excessive sweating and symptoms of heart failure during infancy. The girl was suspected to have ALCAPA clinically and echocardiographically finally selective right coronary arteriography established the diagnosis. Keywords: Congenital heart disease; ALCAPA. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9397 Cardiovasc. J. 2011; 4(1): 92-95